Taxonomic importance of seed morphology of Veronica L. subsect. Agrestes Benth. (Plantaginaceae) - Mazur, Małgorzata; Gawlak, Magdalena; Sandurska, Elżbieta; Kałuski, Tomasz; Marcysiak, Katarzyna (Biodiversity: Research and Conservation, 2018)
The study was conducted on five species of Veronica L. subsection Agrestes occurring in Central Europe: Veronica agrestis L., V. polita Fr., V. opaca Fr., V. persica Poir. and V. filiformis Sm. These species are very similar morphologically and are often misidentified. Last thorough studies of morphology and micromorphology of their seeds were conducted in 1960s. Based on 48 herbarium specimens, we examined SEM images of 422 seeds. We found that 22 of the 30 studied morphological traits differentiated five species at statistical level and V. agrestis and V. persica differed with the greatest number of features from other species. Our measurements of seed size were not fully congruent with previous studies, suggesting dependence of these features on external conditions. Seeds were usually cochlidiospermous and ovoid with a reticulate-verrucate seed coat, but these features were, at the same time, quite variable. The results of discriminant function confirmed that some characters of the seed size, shape and coat sculpture could be taxonomically useful in distinguishing species of Veronica subsect. Agrestes. In addition, we believe that similarity of the examined seeds may confirm unity of this group and the need of identifying a subsection.